Site-vegetation relationships in the montane zone of northern Colorado - Geist, J. Michael, author; Mogren, Edwin W., advisor; Terwilliger, Charles, Jr., advisor; Ward, Richard T., committee member; Johnson, Donald D., committee member (Colorado State University. Libraries, 1965)
A means of determining the suitability of sites in the montane zone of northern Colorado for production of ponderosa pine and the native herbaceous vegetation from soil and landscape characteristics has not previously been developed. The objectives of this study are to identify the site factors important in determining the productivity of an area for both of these crops, and to develop a growth prediction equation, utilizing these factors, for each of the crops. Twenty sites, which spanned a continuous range of productivity, were located in portions of the Cache La Poudre River watershed in Larimer County, Colorado, Each site was investigated to determine the physical soil and landscape characteristics. Chemical soil characteristics were determined from analyses of soil samples obtained in the field. Production measurements of both crops were made at each site, also. Correlation coefficients (r) were computed between measured site factors and productivity. Some of the significantly correlated factors were used as independent variables to develop a multiple linear regression equation for each crop. The following expressions resulted, with independent variables listed in decreasing order of importance to prediction of Y: for the ponderosa pine equation Y (5-year growth index) = : +79.13 (regression constant) -.7346 X1 (percent slope) +13.63 X2 (log10 effective depth of the A horizon) -.8505 X3 (weighted mean percent clay in the A) -.0038 X4 (elevation) -.0129 X5 (weighted mean percent sand in the A) for herbaceous vegetation equation Y (mean annual herbaceous production) = : -1279 (regression constant) +17.56 X1 (cation exchange capacity index of the A horizon) +15.56 X2 (exchangeable magnesium index of the A horizon) -.9786 X3 (K2O in the A) -3.629 X4 (exch. Ca index of the A) -6.180 X5 (organic matter in the A) +.1916 X6 (elevation) +10.49 X7 (percent slope) +18.36 X8 (effective depth of the A). The multiple coefficient of determination (R2) for the ponderosa pine prediction equation was 0.66 and the R2-value for the herbaceous vegetation prediction equation was 0.84. The coefficient of variation of Y was 23.7 percent for the ponderosa pine equation and 63.3 percent for the herbaceous production equation. Correlation coefficients indicated that ponderosa pine height growth was positively correlated with the log effective depth of the A horizon, elevation, and weighted mean percent sand in the A. Negative correlations existed between height growth and the percent slope and weighted mean percent clay of the A horizon. Herbaceous production was positively correlated with all independent variables shown in the growth prediction equation except percent slope.
Author's name on piece is Jon M. Geist.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Forest soils -- Colorado